Impact of Sijilmasah in the Cultural Arena of Algeria, South of the Sahara:a Study of the Manuscript “At-tinilaniy’s Bibliography 1189 AH” - جعفري , أحمد (Milev Journal of Research and Studies, 2020)
The city of Sijilmasah historically formed an important point in the history of cultural relationship between cities of the entire Islamic North Africa due to its strategic location that made it a meeting point between the cities of the area, coupled with its conspicuous role in in carrying out cultural activities across periods. This made it one of the most important intellectual cities having strongest contact with Tout area, south of the Sahara. Citation of the manuscript “At-tinilaniy’s bibliography (1189 AH)” remains one of the most important and valuable Algerian manuscripts that records vividly the presence and relationship between Sijilmasah and Tout Algerian cultural activities. This research aims at portraying this important relationship.